Alternatif Design of Compliant Mechanism Based Ankle Foot Prosthesis - Wahyu Dwi Lestari; Ndaru Adyono; Ahmad Khairul Faizin; Dhian Satria Yudha Kartika; Tri Lathif Mardi Suryanto; E I Bhiftime (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
People with permanent disabilities such as transtibial amputees can be independent and lead normal lives through prosthetics. Foot prosthetics is currently a custom product that is adapted to the features of the amputated leg, so it is more expensive and time consuming. Artificial foot products in Indonesia are still dominated by imported products, so they have high prices and are difficult to reach for lower-middle class amputees. The purpose of this study was to create an alternative design of the ankle foot for users of below-knee prosthetics. The design was made using Solidwork software. Two types of alternative ankle foot designs were produced in this study. Both designs apply a compliant mechanism system to make it more flexible when used. The design is made to meet one of the specified criteria, namely light weight with a mass of less than 2.3883 kg. Three alternative materials are offered in both design alternatives, namely Acrylonitrile Butadiene Styrene (ABS), Poly Oxy Methylene (POM), and AISI 304. Based on the design, it is found that the lightest design is owned by an alternative ankle foot design 1 with ABS material that is equal to 62.69 gram.